2015
DOI: 10.1016/j.metabol.2015.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Cord blood irisin levels are positively correlated with birth weight in newborn infants

Abstract: Background Irisin is a novel myokine, secreted from skeletal muscle after exercise. Irisin mediates exercise-related energy expenditure by turning white adipose tissue (WAT) into brown adipose tissue (BAT). Thus, irisin is considered as a potential biomarker for obesity and metabolic syndrome. Infants born small for gestational age (SGA) have increased risk for metabolic syndrome. However, the physiologic role of irisin in neonates remains to be studied. Objective To evaluate the association of umbilical cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 27 publications
3
22
0
3
Order By: Relevance
“…In the present study, we found that serum irisin levels were at a few μg/ml. However, circulating irisin levels have been reported at μg/ml [3,20], ng/ml [21,22], and even pg/ml [23,24] levels in different studies. In most studies, irisin levels were measured by ELISA.…”
Section: Disease Markersmentioning
confidence: 96%
“…In the present study, we found that serum irisin levels were at a few μg/ml. However, circulating irisin levels have been reported at μg/ml [3,20], ng/ml [21,22], and even pg/ml [23,24] levels in different studies. In most studies, irisin levels were measured by ELISA.…”
Section: Disease Markersmentioning
confidence: 96%
“…They also observed that irisin was positively correlated with birth-weight. Similarly, Joung et al [23] reported lower irisin in SGA than AGA and LGA, and that irisin was positively associated with gestational age and birth-weight. The authors speculated that lower irisin levels in SGA may contribute to the development of catch-up growth and metabolic syndrome later in life, which remains to be elucidated by further mechanistic studies.…”
Section: Study Aim Main Findingsmentioning
confidence: 81%
“…Joung (2015) [23] Humans; cross-sectional Evaluation of cord blood irisin in LGA, SGA and AGA in newborns (26-41 weeks' gestation).…”
Section: Study Aim Main Findingsmentioning
confidence: 99%
“…Newborn infants have a higher content of BAT required for thermogenesis and its percentage declines after infancy. Appropriate gestational age (AGA) infants have higher total body fat percentage as compared to smaller gestational age (SGA) infants which is a consequence of lower irisin level [52,53]. A cross-sectional study conducted by Caglar and his colleagues [54] explained the relation between cord blood irisin level and birth weight.…”
Section: Role In Pregnancy and Infantsmentioning
confidence: 99%